Organizing Community Participation in Watershed Management - Maitra, M.K. (Journal of Soil and Water Conservation, 2022)
In order to bring about community participation in watershed management, it is important that conceptual clarity about the scopes of such participation be made clear. If in a given situation, participatory development in its trite sense is considered unattainable, even partial participation may be useful to begin with, provided the limitations are openly recognized and the ultimate goal of empowerment be kept clear to mind. One useful way of capacity building is to involve the communities in planning and implementation of the project. The technique of Participatory Rapid Appraisal (PRA) when applied in the right perspective not only permits incorporation of community preferences into the planning process but also allows meaningful implementation of the project' even on the basis of a skeletal plant. Since, even the most detailed technically sound planning does not necessarily guarantee sound results, the scope of keeping the planning a simultaneous dynamic process should be studied.. Another important prerequisite for sustained community participation is the formation of an effective people's organization which functions democratically and is capable of implementing community decisions.